The composition and diversity of plant species in pasak bumi’s (Eurycoma longifolia) habitat in Batang Lubu Sutam forest, North Sumatra, Indonesia - ARIDA SUSILOWATI; HENTI HENDALASTUTI RACHMAT; DENI ELFIATI; M. HABIBI HASIBUAN (Biodiversitas Journal of Biological Diversity, 2019)
Susilowati A, Rachmat HH, Elfiati D, Hasibuan MH. 2019. The composition and diversity of plant species in pasak bumi’s (Eurycoma longifolia) habitat in Batang Lubu Sutam forest, North Sumatra, Indonesia. Biodiversitas 20: 413-418. Pasak bumi (Eurycoma longifolia Jack) is one of the most popular medicinal plants in Indonesia. Currently, E. longifolia is being over-exploited due to its potential and popularity as herbal medicine and its high value in the market. Therefore, the study on the population structure of the species and habitat characterization is required to ensure successfulness of conservation of this species. The study was carried out in lowland forest, located in Limited Production Forest within the Register Number 40, situated administratively in Papaso Village, Sub-District of Batang Lubu Sutam-Padang Lawas, North Sumatra, Indonesia. Batang Lubu Sutam forest is known as a source of pasak bumi material in North Sumatra. Every year tons of pasak bumi are collected from this forest and exported to Malaysia and surrounding countries. Due to illegal harvesting for its roots, pasak bumi has been seriously depleted in some areas in Batang Lubu Sutam forest. Therefore, current data on its population are needed for conservation effort of Batang Lubu Sutam's pasak bumi. The objectives of this study were to assess the structure of forest where pasak bumi grows and to determine the correct management for sustainability the future stocks. Vegetation analysis was carried out purposively in four transect belts, each consisting of five quadrats or plots. The results showed that the Importance Value Index of pasak bumi at seedling, sapling, pole and tree stages was 21.26%, 9.147%, 0, and 0 respectively. The Shannon Diversity Index (H) ranged between 3.050 and 3.220 and was inside its common value distribution. The evenness index was high, more than 0.85, at all stages of plant growth. The disappearance of pasak bumi at pole and tree stages indicates threatening condition for the sustainability of pasak bumi in the study sites because of excessive harvesting.